2011
DOI: 10.4172/jbb.1000065
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Final Year Medical Students in Iraqi Universities about Generic Medicines

Abstract: Objective: To explore and evaluate final year medical students' perceptions of and knowledge about generic medicines in Iraqi universities. Methods:A cross-sectional survey was conducted between 1 st June 2010 and 31 st July 2010 in six Iraqi public universities offering courses in medicine. Results:Responses were received from 546 medical students (response rate 69.6%).More than 60% of study participants thought that generic medicines are inferior, less effective and produce more side effects compared to bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
6
8
0
Order By: Relevance
“…This is in line with the studies conducted in Australia and Iraq (18,19). This may have a negative impact on the students' prescription habits while practicing upon graduation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is in line with the studies conducted in Australia and Iraq (18,19). This may have a negative impact on the students' prescription habits while practicing upon graduation.…”
Section: Discussionsupporting
confidence: 78%
“…This could be mainly due to the lack of knowledge about these products and their relationship to each other, where 61.8% of the respondents were not introduced to the issues of bioequivalence for generic drugs during their education. Similar findings were reported for Australian and Iraqi final-year medical students (18,19), where 72.0 and 75.0% of the students did not believe that generic medicines are therapeutically equivalent to their corresponding brand medicines, respectively. Compared to only 8.7% of the respondents in the present study who showed a need for information about the bioequivalence of generic medicines during their medical education, 68.0% and 75.0% of Australian and Iraqi medical students showed such a need, respectively.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[7] Majority respondents agreed that generic products rated as "generic equivalents" are therapeutically equivalent to the innovator brand product as well as to each other [2,8] but almost half of them could not answer the correct range for bioequivalence criteria set by the Drug Control Authority of Malaysia, a finding similar to previous reports. [5,9,10] In contrast to earlier reports that contradict our findings showing that respondents, more than 70% [8] and 43.3%, [11] this study showed that the majority of the respondents perceived generic medicines as bioequivalent to innovator medicines. [2] At the same time, nearly half of our respondents believed that innovator medicines are required to meet higher safety standards than generic medicines.…”
Section: Discussionmentioning
confidence: 58%
“…This reflected the deficiency in students' knowledge about pharmacokinetic parameters in establishing bioequivalence of generic medicines, although this topic had been covered in their pharmacy curricula. [2,8] This was probably due to the lack of bridging between the knowledge of bioequivalence testing to generic medicines.…”
Section: Discussionmentioning
confidence: 97%